Mires from pole to pole - Lindholm, Tapio; Heikkilä, Raimo (Finnish Environment Institute, 2013)
Mires from pole to pole is a proceedings volume of the XII biennial International Mire Conservation Group symposium held in Finland 24.-27.7. 2006. The following topics are included in the volume: 1. Towards the understanding of the variety of mires and their conservation in different countries, 2. Patterns in polygon mires in north-eastern Yakutia, Siberia: The Role of Vegetation and Water, 3. Mires on the map of Russia, 4. Development of the large-scale hydrotopography of aapa mires on the land-uplift coastland in northern Finland, 5. The development of patterning on a succession series of aapa-mire systems on the land-uplift coast of northern Ostrobothnia, Finland, 6. The beginning of agriculture in Swedish Lapland, 7. Moss diversity in the mires of the Maanselkä water divide, 8. Vegetation studies and mapping in Juortanansalo mire reserve, eastern Finland, 9. Holocene vegetation dynamics and carbon accumulation of two mires in the Friendship Park, eastern Finland, 10. Vegetation dynamics of the Ileksa-Vodlozero aapa mires, 11. Vegetation of forested mires in the middle boreal subzone of Karelia, 12. Mire flora, vegetation and conservation in the Republic of Karelia, Russia, 13. Mire types of the southern part of Kenozero National Park, Arkhangelsk region, NW Russia, 14. Postdrainage vegetation dynamics in mesotrophic herb-Sphagnum mires of southern Karelia, Russia, 15. The Finnish peat mining paradox: political support to environmental calamity, 16. Nationally and regionally threatened mire mosses in Finland, 17. Assessment of threatened mire habitats in Finland, 18. Monitoring restored peatlands in Finnish nature reserves, 19. Species richness and abundance of butterflies in natural and drained mires in Finland, 20. Impacts of peatland restoration on nutrient leaching in western and southern Finland, 21. Role of protected areas in maintaining the diversity of peat mosses in the Karelian Isthmus and Gulf of Finland islands (Leningrad Region, northwest Russia), 22. Sphagnum cover surface shape variations ...